In vitro study of staining agents effects on optical properties of esthetic restorative materials - Dinelli, Welingtom [UNESP]; Fernandes, Renata Vidal [UNESP]; Andrade, Marcelo Ferrarezi de [UNESP]; Guimarães, Norberto Catanzaro [UNESP]; Bevilacqua, Flavia Magnani (My University, 2010)
The authors have studied the effect of four staining agents on the optical properties of esthetic restorative materials through translucency tests. Two commercial brands of composite resins were used: Point 4 (Kerr) and Charisma (Heraeus-Kulzer). The liquids tested were: wine, cola, chlorhexidine solution and nicotine solution. The translucency was measured at different periods of time: P0 – before immersion (baseline), P1 - 1 h after immersion, P2 - 2 h after immersion and successively, P3 – 24 h after immersion up to a period of 7 weeks. ANOVA statistical analysis was applied to the data (p < 0.05). The results lead to the following conclusions: (1) Composite resins submitted to the tested immersion mediums were stained, (2) the lower percentage of translucency was observed for nicotine containing solution, (3) The percentage of translucency decreased with the period of immersion.
Keywords: Composite resin; dental materials; translucence